Controls on the distribution of fluorescent dissolved organic matter during an under‐ice algal bloom in the western Arctic Ocean - Mendoza, Wilson G. (Global Biogeochem Cycles, 2017)
In this study we used fluorescence excitation and emission matrix spectroscopy, hydrographic data, and a self‐organizing map (SOM) analysis to assess the spatial distribution of labile and refractory fluorescent dissolved organic matter (FDOM) for the Chukchi and Beaufort Seas at the time of a massive under‐ice phytoplankton bloom during early summer 2011. Biogeochemical properties were assessed through decomposition of water property classes and sample classification that employed a SOM neural network‐based analysis which classified 10 clusters from 269 samples and 17 variables. The terrestrial, humic‐like component FDOM (ArC1, 4.98 ± 1.54 Quinine Sulfate Units (QSU)) and protein‐like component FDOM (ArC3, 1.63 ± 0.88 QSU) were found to have elevated fluorescence in the Lower Polar Mixed Layer (LPML) (salinity ~29.56 ± 0.76). In the LPML water mass, the observed contribution of meteoric water fraction was 17%, relative to a 12% contribution from the sea ice melt fraction. The labile ArC3‐protein‐like component (2.01 ± 1.92 QSU) was also observed to be elevated in the Pacific Winter Waters mass, where the under‐ice algal bloom was observed (~40–50 m). We interpreted these relationships to indicate that the accumulation and variable distribution of the protein‐like component on the shelf could be influenced directly by sea ice melt, transport, and mixing processes and indirectly by the in situ algal bloom and microbial activity. ArC5, corresponding to what is commonly considered marine humic FDOM, indicated a bimodal distribution with high values in both the freshest and saltiest waters. The association of ArC5 with deep, dense salty water is consistent with this component as refractory humic‐like FDOM, whereas our evidence of a terrestrial origin challenges this classic paradigm for this component.